2013
DOI: 10.1530/eje-12-0864
|View full text |Cite
|
Sign up to set email alerts
|

Granulation pattern, but not GSP or GHR mutation, is associated with clinical characteristics in somatostatin-naïve patients with somatotroph adenomas

Abstract: Objective: Somatotroph adenomas causing acromegaly are histologically classified into densely granulated (DG) and sparsely granulated (SG) subtypes with different morphology, clinical characteristics and treatment outcomes. Granulation pattern has been reported to co-segregate with a recurrent mutation at codon 49 in growth hormone receptor (GHR) and GSP oncogene. This study examines response to the octreotide suppression test (OST) in relation to granulation pattern and mutation in GHR and GSP. Design: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 42 publications
11
77
2
5
Order By: Relevance
“…A mixed phenotype was assigned when more than 30% of tumour cells deviated from the dominant Cam5.2 pattern. The immunohistochemical methods for determination of granulation pattern and the sequencing of GNAS have been previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…A mixed phenotype was assigned when more than 30% of tumour cells deviated from the dominant Cam5.2 pattern. The immunohistochemical methods for determination of granulation pattern and the sequencing of GNAS have been previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…SG subtypes occur in younger patients, are larger, more invasive, and less responsive to SSA (Larkin et al 2013). Various other invasiveness and/or tumor aggressiveness markers have been proposed.…”
Section: Pathologymentioning
confidence: 99%
“…In a large national-registry-based analysis, 'safe' (!2 mg/l) GH levels were achieved with long-term SSA treatment in 75%, normal IGF1 in 69% and both in 55% of cases. Adenomas with a DG cytokeratin pattern (Larkin et al 2013), high SSR2 and SSR5 expression (Espinosa de los Monteros et al 2014), low Ki-67 index (Kasuki et al 2012), as well as those previously subjected to surgery and/or RT (Howlett et al 2013) respond better to SSA treatment.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…The implication of gsp mutation in SSA response has been widely discussed (Larkin et al 2013); nevertheless, a recent meta-analysis revealed that GNAS-positive patients have an approximately 10% greater reduction in GH levels in response to an acute octreotide suppression test (Efstathiadou et al 2015). Additionally, GNAS positive patients show high levels of SSTR2 mRNA (Taboada et al 2011) and low levels of sst5TMD4 .…”
Section: Gnas Mutationmentioning
confidence: 99%
“…Cytokeratin staining is used in clinical practice to characterise densely granulated adenomas having cytokertain staining with perinuclear pattern and sprasely granulated adenomas having dot-like pattern (Obari et al 2008). Sparsely granulated somatotrophinomas occur in younger patients, are larger and more invasive than densely granulated tumours and typically express SSTR5 but not SSTR2 (Mayr et al 2013), while densely granulated adenomas present higher levels of SSTR2 and are more responsive to SSA treatment (Obari et al 2008, Fougner et al 2012, Kato et al 2012, Brzana et al 2013, Larkin et al 2013.…”
Section: Granulation Patternmentioning
confidence: 99%